Comparison of effect of isobaric bupivacaine vs hyperbaric bupivacaine on haemodynamic variables in thorcic combined spinal epidural anaesthesia for laparoscopic cholecystectomies - Kour, Loveleen; Gupta, Kuldip C. (International Journal of Research in Medical Sciences, 2018)
Background: Regional anaesthesia has always been an attractive option for laparoscopic surgeries in patients who are not fit for general anaesthesia. Also, regional anaesthesia has certain advantages over general anaesthesia like lesser oropharyngeal morbidity, lesser blood loss and decreased chances of thrombosis. Lumbar spinal anaesthesia has been synonymous with the term regional anaesthesia for laparoscopic surgeries for quite some time now. In the light of recent works by Imbelloni and Zundert, thoracic spinal anaesthesia has been shown to be a promising alternative not only for healthy patients but for high risk patients as well. Baricity defines the density of the drug with respect to CSF density. This undoubtedly makes it is one of the most important factors that influence drug distribution in the subarachnoid space. Drugs of differing baricities have been studied previously in lumbar spinal anaesthesia. We aimed at studying the behaviour of isobaric and hyperbaric bupivacaine using a different approach which in this study was thoracic combined spinal epidural anaesthesia. Authors evaluated the haemodynamic changes as well as neurological and any other post operative complications that occurred in any of the patients. Methods: There were 60 ASA I and II patients undergoing elective laparoscopic cholecystectomy who were chosen for this study. They were randomly divided into two equal groups - group I and group H. Thoracic combined spinal epidural anaesthesia (CSE) was performed at T9-T10 / T10-T11 interspace. Patients in group I received 1.5ml of isobaric bupivacaine 0.5% (5mg/ml) + 25µg (0.5ml) of fentanyl and group H patients were given 1.5ml of hyperbaric bupivacaine 0.5% (5mg/ml) + 25µg (0.5ml) of fentanyl. Results: There was no significant difference among the haemodynamic variables between the two groups and no neurological complication was seen in any patient. Conclusions: Thoracic combined spinal epidural anaesthesia allows haemodynamic stability in laparoscopic cholecystectomies with minimal neurological and post operative complications irrespective of baricity of the drug used.